Performance Improvement of Reading Brain Function Considering Quantified Analysis of Highly Specialized Neurons: A Neural Networks Approach - Hassan M. H. Mustafa (New Ideas Concerning Science and Technology Vol. 10, 2021)
This piece of research adopts the conceptual approach of (ANN) models inspired by functioning of highly specialized biological neurons in reading brain based on the organization the brain’s structures/substructures. Additionally, in accordance with the prevailing concept of individual intrinsic characterized properties of highly specialized neurons, presented models closely correspond to performance of these neurons for developing reading brain in a significant way. More specifically, introduced models concerned with their important role played in carrying out cognitive brain function’ outcomes. The cognitive goal for reading brain is to translate that orthographic word? from into a spoken word (phonological word?form). In this context herein, the presented work illustrates via ANN simulation results: How ensembles of highly specialized neurons could be dynamically involved in performing the cognitive function of developing reading brain. This study shows that flock of neurons interacts together among the flock’s agents to perform a specific common role (Reading function) via visual and auditory brain areas.